NILAI-NILAI MORAL YANG TERDAPAT DALAM KABA PADA KESENIAN RABAB (Studi pada Sebuah Pertunjukan Kesenian Rabab di Nagari Duku Kecamatan Koto XI Tarusan Kabupaten Pesisir Selatan Sumatera Barat) - Anita, Yesi; Nurman, Nurman; Frinaldi, Aldri (Humanus, 2012)
This research aims to reveal religious and moral values in kaba (a type of Saga in Minangkabau literature) and rabab Pasisie (a type of percussion in Minangkabau particularly the one from Pesisir Selatan regency). The research is qualitative descriptive. The data, primary and secondary, is collected by observation, interview, and documentation. The interviewees are selected through purposive sampling. The data is then tested by triangulation of the sources, and then analysed using selection, reduction, classification, and presentation of data, which is later concluded. The result shows that rabab Pasisie is still fancied by the communities in Nagari Duku Kecamatan Koto XI of Tarusan District. The research concludes that kaba and rabab Pasisie embodies moral values that can be applied in the daily life of the community. We suggest that the leader of Nagari Duku Kecamatan Koto XI of Tarusan District promulgate the traditional rabab as a consideration to make it cultural tourism, while the Minangkabau society can implement moral values in kaba, and it is important that the district’s youth continue to learn and play rabab to maintain the traditional arts. Key words: Minangkabau kaba, rabab Pasisie, moral values, arts